STRATEGI KOLABORASI LEMBAGA AMIL ZAKAT DENGAN PEMERINTAH DALAM PENCAPAIAN SDGS - Silam, Muhammad Mochtar Mandala; Rosdaniah, Rosdaniah; Santoso, Cahyo Budi; Semmawi, Ramli; Syahril, Syahril (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the collaborative strategy between zakat institutions and the government in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia. The approach used was qualitative with descriptive research. Data were obtained through interviews, observation, and documentation, involving zakat institution managers, government officials, and beneficiaries (mustahik). Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The results indicate that collaboration between zakat institutions and the government has contributed to poverty alleviation, increased access to education, and health services. However, this collaboration has not been optimal due to obstacles such as lack of coordination, lack of data integration, and differences in program approaches. Therefore, more effective strategic collaboration is needed through integration programs, strengthening integrated data systems, utilizing digital technology, and increasing human resource capacity. This study concludes that synergistic collaboration between zakat institutions and the government has significant potential for achieving the SDGs sustainably in Indonesia